MARGINALISASI PETANI RUMPUT LAUT PADA MASYARAKAT PESISIR DESA KAMPUNG TOYAPAKEH KECAMATAN NUSA PENIDA, KLUNGKUNG - Anshori, Ivan; Punia, I Nengah; Zuryani, Nazrina (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
This Marginalization of seaweed farmers in Kampung Toyapakeh Village is a condition where local people who work as seaweed farmers don’t have the space and opportunity to do all their activities. The situation is caused by the development of tourism industry in the Kampung Toyapakeh Village because it has the potential of a stunning natural beauty. The problem studied in this research is about how the process of marginalization of seaweed farmers in coastal communities of Kampung Toyapakeh Village, then what causes the marginalization of seaweed farmers, and what impacts are caused. The hegemonic theory of Antonio Gramsci is used in analyzing the problems that occur. Gramsci states that hegemony is a chain of victory gained through consensus mechanisms rather than through oppression of other social classes. The findings show that in Kampung Toyapakeh Village there is a over land function and livelihood function. The government supports the development of tourism and community sectors are included in the development of tourism sector so that there is a shift of livelihood from the agricultural sector into the tourism sector. Keywords: Marginalization, Seaweed Farmers, Over Land Function, Tourism